Effect of exercise training on psychological outcomes in adults with overweight or obesity: A systematic review and meta‐analysis. (6th May 2021) - Carraça, Eliana V.; Encantado, Jorge; Battista, Francesca; Beaulieu, Kristine; Blundell, John E.; Busetto, Luca; van Baak, Marleen; Dicker, Dror; Ermolao, Andrea; Farpour‐Lambert, Nathalie; Pramono, Adryan; Woodward, Euan; et al.
Summary: This study systematically identified the effects of exercise on multiple psychological outcomes among adults with overweight/obesity, also assessing whether these effects differed across exercise types, genders, age, and body mass index (BMI) categories. Pubmed, Web of Science, PsychInfo, and SportDiscus were searched up to October 2019 for peer‐reviewed papers assessing exercise training effects on psychosocial outcomes in adults with overweight/obesity. Thirty‐six articles, 32 randomized controlled trials (RCTs), were included in this review. Most interventions were supervised (65%), ranging between 6 and 76 weeks (median = 12). Sixteen psychological outcomes were studied. Exercise induced positive changes in quality of life but did not reduce depression. Large effect sizes were observed on quality of life's physical component, but exercise was also able to improve vitality and mental health. Most psychological outcomes (e.g., body image, anxiety, and perceived stress) are poorly studied, evidencing either conflicting or null exercise effects. Exercise self‐efficacy and autonomous motivations were also consistently improved. Exercise types and gender seem to moderate exercise psychological effects. Exercise training programs might lead to positive changes in some psychological outcomes, especially in quality of life, in adults with overweight and obesity, but more studies, with greater systematization in program characteristics, and longer follow‐ups are still required to allow more solid conclusions.